Application of SDN and NFV technology in the cloud data center - Hui ZHAO; Ming DING; Qingsong CHENG; Ling LU; Chensheng KONG (Dianxin kexue)
Taking the cloud computing data center as the breakthrough point,firstly,the characteristics of overlay network,SDN controller and VxLAN in SDN field were presented.Secondly,two kinds of problems about general server performance and service chain were analyzed in NFV field.Finally,the early test progress of SDN/NFV technology and related conclusions were expounded,then VDC was discussed.